Taenia solium Prevalence in Nepal: A Retrospective Review - K C, B.; Kaphle, K. (Nepalese Veterinary Journal, 2019)
Taenia solium is a zoonotic cestode parasite which causes cysticercosis in human and porcine cysticercosis in pigs. The infective stage of T. solium develops in pig while that of T. saginata develop in cattle and buffalo. The adult stages of T. solium are obligatory intestinal parasites for man. In humans the cysticercus larvae commonly encyst in the brain, causing neurocysticercosis. The disease was first described in pig by Aristophanes and Aristotle in 3rd century B.C. In Nepal, Taenia cysts were observed for first time in pork meat slaughtered in Kangeswari, Kathmandu more than 30 years ago. T. solium is the cause of 30% of epilepsy cases in many endemic areas where people and roaming pigs live in close proximity. More than 50 million of the world’s populations are infected worldwide and 50000 die from Neurocysticercosis yearly. In Nepal, the prevalence ranges from 0.002-0.1% in general population. Accurate diagnosis required detailed post mortem examination involving slicing of affected tissue to determine the viability of cysts. Cysticerci occur most commonly in striated muscles tissues and brain of pigs. The application of vaccination with TSOL18 recombinant vaccine along with oral medication of oxfendazole can reduces the transmission by pigs whereas use of niclosamide is found effective in humans. Hence the use of medication eventually reduces the incidence of neurocysticercosis in human and procine cysticercosis in pigs.